"A Hindu is white although he is black": Hindu Alterity and the Performativity of Religion and Race between the United States and the Caribbean. (20th January 2016) - Rocklin, Alexander
Abstract: This essay uses the controversies surrounding the enigmatic Ismet Ali, a yogi working in Chicago and New York in the 1920s, to illuminate the complexities of how the performativity of religion and race are interrelated. I examine several moments in which Ali's "authenticity" as Indian is brought into doubt to open up larger questions regarding the global flows of colonial knowledge, racial tropes, and groups of people between India, the United States, and the Caribbean. I explore the ways in which, in the early twentieth-century United States, East Indian "authenticity" only became legible via identificatory practices that engaged with and adapted orientalized stereotypes. The practices of the yogi persona and its sartorial stylings meant to signify "East Indianness" in the United States, particularly the donning of a turban and beard, were one mode through which both South Asian and African Americans repurposed "Hindoo" stereotypes as models for self-formation. By taking on "Hindoo" identities, peoples of color could circumvent the U.S. black/white racial binary and the violence of Jim Crow. This act of racial passing was also an act of religious passing. However, the ways in which identities had to and could be performed changed with context as individuals moved across national and colonial boundaries.